Urinary tract infection in premature rupture of membrane (PROM): an academic hospital based study - Pangastuti, Nuring; Rahman, Muhammad Nurhadi; Liligoly, Rivaldi D (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Premature rupture of membrane (PROM) and preterm PROM (PPROM) are commonly related with poor maternal and perinatal outcomes. Urinary tract infection (UTI) has been known as one of its risk factors. The aim of study was to ascertain the frequency and pattern of urinary symptoms as well as the risk factors for UTI in PROM and PPROM. A retrospective study was conducted at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. All pregnancy cases with the history of PROM/PPROM from January to December 2015 were included. The research subjects were obtained from medical records, using the format of basic data collection to identify the risk factors of UTI in pregnancy. One hundred cases of complicated pregnancy with either PROM or PPROM were obtained. The mean of maternal age, gestational age, and birth weight were 28 ± 5.99 yr; 34.05 ± 4:28 wk; 2170.79 ± 835.447 g; respectively. Urinalysis was done in 58 patients. The prevalence of bacteriuria was 55.17%. Symptomatic vs. asymptomatic bacteriuria showed statistically significant differences (p